2017
DOI: 10.1111/jfpp.13455
|View full text |Cite
|
Sign up to set email alerts
|

In‐house validation of real‐time PCR methods for detecting the INV A and TTR genes of Salmonella spp. in food

Abstract: The microbiological standard method for the detection of Salmonella spp. is time‐consuming, and consequently there is a need for an alternative rapid methodology for its detection. In this study, two open‐formula real‐time PCR methods for detecting the inv A and ttr gene Salmonella spp. have been successfully optimized and in‐house validated. Different DNA extraction procedures were used (boiling, Chelex resin and standard I ‐ Biorad). The relative sensitivity and false positive ratio for the alternative metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Rahn et al (1992) confirmed that this invA gene (gene encoding the invasionassociated protein) contains sequences unique to Salmonella and demonstrated that the invA gene is an appropriate PCR target, with possible diagnostic applications. By then, this gene was used for identification of Salmonella in many studies as with the current study (Shabarinath et al, 2007;Bhowmick et al, 2011;Yang et al, 2016;Dmitric et al, 2018;Yang et al, 2018). All the Salmonella isolates of the present study harbor the invH gene as it was shown by positive PCR (Table 03, Figure 01).…”
Section: Presence Of Virulence Genesmentioning
confidence: 55%
“…Rahn et al (1992) confirmed that this invA gene (gene encoding the invasionassociated protein) contains sequences unique to Salmonella and demonstrated that the invA gene is an appropriate PCR target, with possible diagnostic applications. By then, this gene was used for identification of Salmonella in many studies as with the current study (Shabarinath et al, 2007;Bhowmick et al, 2011;Yang et al, 2016;Dmitric et al, 2018;Yang et al, 2018). All the Salmonella isolates of the present study harbor the invH gene as it was shown by positive PCR (Table 03, Figure 01).…”
Section: Presence Of Virulence Genesmentioning
confidence: 55%
“…More specifically, the ttr gene, which encodes for the tetrathionate reductase, was targeted for the detection of Salmonella spp. as tetrathionate respiration should be genetically stable within the genus [ 39 , 40 ]; the gene hly , encoding for the listeriolysin O, was chosen for the detection of L. monocytogenes , as it has been reported to be relatively well conserved in the species [ 41 , 42 ]; last, the gene rfbE was selected for the specific detection of E. coli O157 as this gene is the one encoding for the “O” antigen of E. coli , and as such, it is highly specific for this serogroup [ 43 , 44 ]. The Tt values obtained were directly compared.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of the number of mutations present in ttr RSBCA, we speculated that the ttr R gene was the most highly conserved, followed by the ttr B and ttr C genes, which have been successfully used in real-time PCR detection of Salmonella in food 10 , 34 . Differences in the prevalence of mutations in the ttr RSBCA cluster may be related to the distinct functions and loci of these genes.…”
Section: Discussionmentioning
confidence: 99%